PENGARUH PEMBERIAN KOMBINASI EKSTRAK KUNYIT PUTIH (CURCUMA ZEDOARIA) DAN DAUN SIRSAK (ANNONA MURICATA L.) TERHADAP KADAR SGOT, SGPT DAN BILIRUBIN TOTAL PADA TIKUS GALUR WISTAR (RATTUS NOVERGICUS) YANG DIINDUKSI KARBON TETRA KLORIDA - Nabila Syafaqoh Fardam N (2022)
Hepatotoxicity is a hepar state that suffers damage due to a fairly long period from the use of a certain substance or various drugs. Carbon tetrachloride (CCl4) can be the cause of damage to hepar function. Combination of white turmeric extract (Curcuma zedoaria) and soursop leaves (Annona muricata L.) Potential to become hepatoprotection. The study aimed to find out if this combination could lower total levels of SGOT, SGPT, and Bilirubin due to damage caused by the induction of carbon tetrachloride (CCl4). The sample consisted of 30 male Wistar strain mice divided into five treatments, namely K- given standard feed and aqudes, K(+) induced CCl4 on day 14, K1 given soursop leaf extract 150 mg / KgBB for 14 days, K2, K3, and K4 given soursop leaf extract 150 mg / kg bb and white turmeric extract 150 mg /kg bb, 300 mg/kg bb, 450 mg/kg bb then induced CCl4 on day 14. The data results were then analyzed using the one-way ANOVA test and the LSD test. The results of the one-way ANOVA test obtained no meaningful difference (P>0.05). LSD test results were significantly different (p<0.05). Conclusion: The combination of white turmeric extract and soursop leaves cannot lower levels of SGOT, SGPT, and Total Bilirubin induced Carbon tetrachloride.